PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA DI MERTHA SUCI BANGLI - Brahmanda Yoga, Agung; Rudy, Dewa Gde; Sandhi Sudarsana, Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
Mertha Suci is a company in Bangli which is run in food sector, expeditions, andthe arts. All of the company must gives legal protection to all its labor. Legal protection oflabor is protection so that the workers can do a decent job for humanity.The type ofresearch is field research and library researchForm of legal protection that has beencarried out in accordance with the terms are 1) Serve nutritious food and drink and bonusfor workers overtime, 3)Provide a break or leave for its workers, and 4) Give first aidfacilities. While, form of legal protection that has Number been carried out are 1) HaveNumber provide the shuttle transportation for the labor and 2) Have Number the differenttoilet for ladies and gentleman. Things that inhibit the implementation of the legalprotection are the economic orientation of the entrepreneur, the labor who are concernedwith the financial without think about the health and safety, and the absence of laws thatclearly addresses the legal protection for workers with physical disabilities, especiallyregarding the protection of wages.
Keywords: legal protection, labor that not old enough